THE APPLICATION OF ENTEROSORBENTS TO TREAT ATOPIC DERMATITIS AMONG CHILDREN - P.L. Shcherbakov; V.A. Revyakina ("Paediatrician" Publishers LLC, 2007)
The article is dedicated to the study of the peculiarities of atopic dermatitis run from the viewpoint of allergistcimmunologist and gastroenterologist. The authors give an analysis of the reasons for atopic dermatitis development conditioned by the food allergy and define the place and meaning of the digestive apparatus function within the mechanisms of the disease development. The authors dwell in detail on the state of the intestinal tract mucosa and peculiarities of its lesion during atopic dermatitis. They give the schemes of the combined treatment for atopic dermatitis aimed at recovery of the affected small bowel mucosa and recovery of its protective properties with the help of cytomucoprotective adsorbing agents. They also present the findings of their own clinical experience of treatment of children, suffering from atopic dermatitis and having various lesions of the digestive apparatus.Key words: atopic dermatitis, children, food allergy, cytomucoprotection, adsorbing agents, dioctahedral smectite.